Antivertiginous Effect of Caloric Stimulation for Acute Peripheral Vertigo. Issue 4 (16th April 2022) - Fukushima, Munehisa; Makino, Saho; Matsumoto, Ken; Okamoto, Hidehiko; Akahani, Shiro; Imai, Takao; Inohara, Hidenori
Abstract : Objective: To clarify therapeutic effect of caloric stimulation for acute peripheral vertigo. Patients: Two patients with acute peripheral vertigo accompanied by spontaneous nystagmus. Interventions: Therapeutic. Main Outcomes and Measures: Changes in the maximum slow phase velocity of spontaneous nystagmus and subjective vertigo. Results: Reduction in the maximum slow phase velocity of spontaneous nystagmus and mitigation of subjective vertigo was observed in both patients. Conclusion: Caloric stimulation could be one potential option as a suppressant for acute peripheral vertigo.